A 3000 year record of Caribbean reef urchin communities reveals causes and consequences of long‐term decline in Diadema antillarum. Issue 1 (28th April 2017) - Cramer, Katie L.; O'Dea, Aaron; Carpenter, Carolina; Norris, Richard D.
Abstract : Urchins are the last abundant grazers of macroalgae on most Caribbean reefs following the historical overexploitation of herbivorous fishes. The long‐spined urchin Diadema antillarum was particularly effective at controlling macroalgae and facilitating coral dominance on Caribbean reefs until its ecological extinction from a catastrophic disease epidemic in the early 1980s. Despite their important role in the structure and functioning of Caribbean reef ecosystems, the natural dynamics of Caribbean reef urchin communities are poorly known due to the paucity of ecological survey data prior to large‐scale human disturbances and the Diadema dieoff. To help resolve the baseline abundances and ecological roles of common urchin taxa, we track changes in urchin abundance and composition over the past 3000 yr from analysis of subfossil urchin spines preserved in reef matrix cores collected in Caribbean Panama. Echinometra consistently dominated the subfossil spine assemblage, while Diadema was consistently rare in the subfossil record in this region. Rather than increasing during a period of heightened human exploitation of their fish competitors and predators, Diadema began declining over a millennium ago. Convergent cross mapping (CCM) causality analyses reveal that Diadema abundance is causally related to coral community composition. Diadema is negatively affected by Acropora cervicornis dominance, likely due to the tight association between this coral and the threespot damselfish, an effective Diadema competitor. Conversely, Diadema positively affects the abundance of the coral Madracis mirabilis, possibly via its control of macroalgae. Causal relationships were not detected among abundances of individual urchin taxa, indicating that inter‐specific echinoid competition is not a factor limiting Diadema recovery. Our detailed record of prehistorical and historical urchin community dynamics suggests that the failure of Diadema to recover over 30 yr after its mass mortality event may be due in part to the prey release of damselfish following the long‐term overfishing of piscivorous fishes.